2023
DOI: 10.1002/ibra.12098
|View full text |Cite
|
Sign up to set email alerts
|

Basic information about memantine and its treatment of Alzheimer's disease and other clinical applications

Abstract: Memantine is a noncompetitive moderate‐affinity strong voltage‐dependent N‐methyl‐D‐aspartate receptor antagonist. It has been used to treat Alzheimer's disease (AD) since 1989. In 2018, it became the second most commonly used drug for the treatment of dementia in the world. AD is nonreversible, and memantine can only relieve the symptoms of AD but not cure it. Over the past half‐century, memantine's research and clinical application have been extensively developed. In this review, the basic composition of mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Choice of ligands. caffeine [18], Curcumin [19], Nicotine [20], and Memantine [21] were selected as ligands based on previous research indicating their potential efficacy against Alzheimer's disease. These ligands were retrieved from NCBI and converted from SDF to PDB format using the Online Smiles Converter.…”
Section: Methodsmentioning
confidence: 99%
“…Choice of ligands. caffeine [18], Curcumin [19], Nicotine [20], and Memantine [21] were selected as ligands based on previous research indicating their potential efficacy against Alzheimer's disease. These ligands were retrieved from NCBI and converted from SDF to PDB format using the Online Smiles Converter.…”
Section: Methodsmentioning
confidence: 99%
“…The FDA has approved memantine to treat moderate and severe AD alone or combined with AChEIs. Studies indicated that memantine alone can benefit patients with moderate to severe AD, enhancing daily activities and cognitive function [ 32 ]. An advantage of memantine is its compatibility with AChEIs, as they work differently and complement each other’s effects without increasing side effects.…”
Section: Current Treatments and Their Limitationsmentioning
confidence: 99%
“…They are utilized to alleviate cognitive impairment and slow down the progression of dementia in AD patients [ 15 ]. Memantine, an NMDA receptor antagonist, has been approved for moderate-to-severe AD [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%